Analytical Study of Physical & Mechanical Properties of Foamed Concrete Using ETABS - Subramani, T; Amul, R (International Journal of Engineering and Technology, 2018)
Foam concrete is a form of aerated lightweight concrete. Foamed concrete has emerged as most industrial fabric in Production Company. Foam concrete is produced while pre-fashioned foam is brought to slurry, the characteristic of froth is to create an air voids in cementâ€“primarily based absolutely slurry. Foam is generated one by one via using foam generator; the foaming agent is diluted with water and aerated to create the froth. The cement paste or slurry set throughout the foam bubbles and whilst the froth being to degenerate, the paste has enough power to keep its form around the air voids. Consequently, this study investigates bodily and mechanical residences of foamed concrete. Ultimately comparative analyses had been finished to decide the relationships the various numerous mechanical homes parameters of the foamed concrete, especially the compressive strength, flexural electricity, splitting tensile electricity. The specimen analysed by means of the usage of the use of e- tab software program.Â Â